Workforce renewal : increasing the quality and quantity of work - Petrina, Bernard H. (Crisp Pub. Menlo ParkUS, 1994)
Defines workforce renewal; identifies the 5 elements which lead to renewal, and explains the seven-step renewal process. Looks at obstacles to, and strategies for renewal.